Problem Solving Ability in the Learning Model of Problem-Based Learning based on Ethnomathematics - Purwanti, Devi; Zaenuri, Zaenuri; Asikin, Mohammad (Journal of Primary Education)
This study has the purpose of analyzing the effectiveness of the Problem-Based Learning model based on ethnomathematics with Selotigo batik motifs in improving students' problem-solving abilities. This study was true experimental design research. The sampling technique was done using random cluster sampling. The sample in this study was Public Elementary School Sidorejo Lor 07 Salatiga as an experimental class and Public Elementary School Sidorejo Lor 03 Salatiga as a control class with a total of 74 students. The data collection was done through observation, documentation, and test method. The data analysis was done using One-Sample t-test, Proportion Test, and Independent Sample t-test. The results showed that the PBL model based on ethnomathematics was effective in improving students' problem-solving abilities. This result was indicated by the average score of students' problem-solving ability in the learning using PBL model based on ethnomathematics which was above the Minimum Completeness Criteria (KKM) with KKM of problem-solving abilities of 75, the proportion of students completeness of problem-solving abilities in PBL model based on ethnomathematics was above 75% of the classical completeness, the average problem-solving ability of students in the PBL learning model based on ethnomathematics is better than the average problem-solving ability of students in the PBL model. Based on the result, it can be concluded that problem-solving in a PBL model based on ethnomathematics is effective in improving the problem-solving ability of students.